TEST THE VALIDITY AND RELIABILITY OF ARABIC LEARNING QUESTIONS - Imaduddin, Muhammad Faris; Maulani, Hikmah; Taufik, Ijlal Haziel (Arabi : Journal of Arabic Studies, 2022)
This study aims to determine the validity and reliability of Arabic language test items for grade II students of an elementary school without a pesantren (Islamic Boarding School) background in Bekasi City. The research method used is descriptive with a qualitative approach. Data collection techniques used in this research were non-test instruments in the form of observation and test instruments in the form of 10 multiple-choice Arabic language questions, adapted to teaching materials at the existing learning level. Data analysis techniques include reducing, presenting, and drawing conclusions from existing data. Based on the data found, the level of validity of the Arabic language test questions from question numbers 1 to 10 provided 60% is in the valid category and 40% is not. While the level of reliability based on Cronbach's Alpha testing technique is at 0.82 which indicates very reliable. It is hoped that the findings of this research have positive implications for teacher knowledge.